Alloying Effect in Low Loaded Rh Catalysts Supported on High Surface Area Alumina on Their Activity in CH4 and NO Decomposition - Costa, Patrick Da; Dutkiewicz, Jarosław; Choque, Valerio; Homs, Narcis; Kornelak, Paweł; Najbar, Mieczysława; Pietraszek, Agnieszka; Piscina, Pilar Ramirez de la; Sobczak, Janusz (IntechOpen, 2012)
None